2003
DOI: 10.1046/j.1440-1843.2003.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tobacco on lung health in China

Abstract: China has the largest production and consumption of tobacco worldwide. It has witnessed a dramatic increase in tobacco consumption over the past two decades, with more than 34.8 million cartons of cigarettes being produced and 34.7 million sold annually. Approximately 67% of males and 4% of females aged over 15 years in China are smokers, and the total of over 320 million Chinese smokers represents about one-third of all smokers worldwide. The continuous, rapid increase in the number of Chinese smokers is larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
100
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(105 citation statements)
references
References 7 publications
3
100
0
2
Order By: Relevance
“…It has been reported that Chinese smokers represent about one-third of all smokers worldwide. 2 There has also been an increase in the incidence of primary lung cancer observed in never smokers, with increased incidence in females and a higher occurrence of adenocarcinoma compared with lung cancer in smokers. 3 Although the etiology of lung cancer in never or light smokers remains indefinite, there are several candidates for risk factors, such as environmental tobacco smoke, cooking fumes, and exposure to radon.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Chinese smokers represent about one-third of all smokers worldwide. 2 There has also been an increase in the incidence of primary lung cancer observed in never smokers, with increased incidence in females and a higher occurrence of adenocarcinoma compared with lung cancer in smokers. 3 Although the etiology of lung cancer in never or light smokers remains indefinite, there are several candidates for risk factors, such as environmental tobacco smoke, cooking fumes, and exposure to radon.…”
Section: Introductionmentioning
confidence: 99%
“…tobacco marketing campaigns [13][14][15]. Especially troubling is the increase in youth smoking and initiation taking place earlier in life [13,16]. Clearly, Chinese public health leaders have an NCD crisis in the works.…”
Section: The Ncd Epidemic In Chinamentioning
confidence: 99%
“…In the last decades, the incidence and mortality rates of lung cancer have been increasing rapidly, especially in regions where tobacco consumption is more common (2). Although many studies have shown that smokingtobacco accelerated lung carcinogenesis, genetic factors still play a key role (3).…”
Section: Introductionmentioning
confidence: 99%